Pengaruh Etos Kerja, Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Pegawai - Yustina Maro; Hermayanti Hermayanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
Performance is the result of work produced by employees through several aspects that must be passed and has stages to achieve it and aims to improve the performance of the employees themselves. This study aims to determine the effect of work ethic, leadership style, and work environment on employee performance either partially or simultaneously. The study was conducted at the Alor Barat Daya District Office, Alor Regency with a population and sample of 40 employees. Data collection techniques using observation, interviews, questionnaires, and literature study. Data analysis using research instrument test, namely validity test, reliability test; classical assumption test, namely normality, heteroscedasticity, multicollinearity, and linearity tests followed by multiple linear regression tests. Hypothesis testing using partial test and simultaneous test. The results showed that either partially or simultaneously work ethic, leadership style, and work environment had a significant effect on employee performance.